Lehigh Technologies' micronized rubber powder process gains ICIS innovation award. Issue 12 (December 2018) - Unknown
Abstract : Georgia, USA-based Lehigh Technologies' innovative approach to end-of-life tyre recycling using cryogenic grinding of tyre rubber to produce micronized rubber powder (MRP) was chosen as the overall winner in the ICIS Innovation Awards for 2018. The company's entry also won in the category for Innovation with Best Benefit to Environment or Sustainability.